"My critical filter buffers your app filter": Social media literacy as a protective factor for body image. (March 2022) - Paxton, Susan J.; McLean, Siân A.; Rodgers, Rachel F.
Highlights: Theories of social media literacy as protective for body image are described. Measurement of social media literacy related to appearance images is reviewed. Some empirical support exists for the protective role of social media literacy. Supportive evidence is found in girls and young women but not boys or young men. More research is needed into relations between social media literacy and body image. Abstract: Exposure to idealized appearance images on social media is recognized as having a damaging effect on body image. Identifying and harnessing protective factors are, therefore, important research foci. Building on traditional media literacy concepts, one proposed protective factor is social media literacy, that is, the application of a critical analysis of motivations behind social media posts and the constructed, generally unrealistic nature of images, when viewing appearance-focused images on social media. This article describes theoretical models of social media literacy and current measurement approaches. In addition, it examines empirical support for a protective role for social media literacy, before considering directions for future research. It was concluded that, although there is still much that needs to be understood, there is modest preliminary support for a protective role for social media literacy, especially in girls and young women.